The values of geodiversity: geosites of the Araripe Geopark, state of Ceará, Brazil - Mochiutti, Nair Fernanda; Guimarães, Gilson Burigo; Moreira, Jasmine Cardozo; Lima, Flavia Fernanda; Freitas, Francisco Idalécio (Anuário do Instituto de Geociências, 2012)
In July 2010 researchers from the State University of Ponta Grossa visited the Araripe Geopark (AG), the only national representative in the Global Network of Geoparks. Accompanied by staff members of the AG, the group looked for knowing the geopark territory, administrative and physical infrastructure, public and private partners, daily work and the whole process of its establishment, with the main objective to build a similar proposal in the Campos Gerais region, State of Paraná. All selected geosites from the AG were visited, and intrinsic, cultural, aesthetic, economic, functional, educational and scientific values of geodiversity, as proposed by Murray Gray in his seminal work, were identified too. Considering the implicit subjectivity, it is assumed that all geosites have an intrinsic value. In relation to the other values, the more easily recognizable to each geosite were: the cultural value for the Colina do Horto Geosite, mainly associated with religious concerns and the figure of Cícero Priest, and the Batateiras and Missão Velha Waterfall geosites, by the strong connection with the Kariri People settlements, their history and legends and their relation with water resources; the aesthetic value for geosites with favorable topographical location and privileged views of Araripe Cuesta and the extension of the sedimentary basin (Colina do Horto and Pontal da Santa Cruz geosites), waterfalls composing an impressive landscape (Batateiras and Missão Velha Waterfall geosites) and exceptional processes of erosion (Ponte de Pedra Geosite); the economic value for Pedra Cariri Geosite, with the mining of laminated limestone, and in the former Ipubi Geosite, with a closed mine of gypsum; the functional value is significant in Batateiras and Riacho do Meio geosites, where springs of major rivers of the region are harbored; and, the whole set of geosites shows scientific and didactic values, but they are prominent in the Cariri Petrified Forest and Pterosaurs Park, with an outstanding paleontological record. The identification of these values reinforces and contextualizes the importance of geoconservation actions that have been conducted in this territory and puts a holistic sight on the geodiversity, strengthening its linkage with the local population and with all life that is supported by this geodiversity.